ESTIMATION OF THERMODYNAMIC EFFICIENCY OF USING EXPANDER -GENERATOR UNIT - Volianska , Larisa; Nikitina, Galyna; Beregovoi , Ivan (Science-based technologies, 2021)
The article considers the possibility of utilizing the energy of excess pressure of natural gas supplied through gas pipelines to gas distribution stations and gas control points of industrial gas consumers. The assessment of the thermodynamic efficiency of the expander of the generator unit is carried out in comparison with the throttling devices when they are used at the gas distribution station and gas control point. The prospects of using the potential pressure energy of main gas pipelines and renewable energy sources for obtaining additional energy have been identified.